An Assessment of the Dominant Organizational Culture among Faculty Members at the Hashemite University in Jordan - Altahayneh, Ziad; Abu-Tineh, Abdullah; Khasawneh, Samer (Jordan Journal of Educational Sciences, 2006)
The main purpose of this study was to determine the dominant organizational culture type as perceived by faculty members at the Hashemite University. A total of 110 faculty members participated in the study by completing the Organizational Culture Assessment Questionnaire (OCAQ).The results showed that respondents moderately practiced the four functions of the organizational culture combined (managing change, achieving goals, cultural strength, and coordinating teamwork). Cultural strength was the most perceived organizational cultural function practiced followed by achieving goals and coordinated teamwork. Managing change was the least perceived cultural function practiced by the participants. Furthermore, the relationship between academic rank and the function of managing change revealed a difference between full professors and assistant professors in the favor of assistant professors